Postoperative speech therapy intervention of the lingual frenulum in children, adolescents and adults. Integrative literature review - Inostroza-Allende, Felipe; Caviedes Ulloa, Cristóbal; González Jara, Matías; Palomares-Aguilera, Mirta (Revista de Investigación en Logopedia, 2022)
In recent years there has been a significant increase in the diagnosis of tongue tie, lingual frenulum surgeries and scientific publications. In this regard, it is necessary for health professionals to know the speech therapy treatment in these cases. The aim of the study was to describe the speech therapy intervention implemented in children, adolescents and adults after frenotomy, frenectomy or lingual frenuloplasty, through an integrative literature review. For this, during the second quarter of 2020 the electronic databases PUBMED, LILACS, SciELO and Cochrane, were consulted using the keywords in English: "Ankyloglossia", "Tongue Tie", "Lingual Frenulum", "Lingual Frenum", "Surgical Procedures", "Frenuloplasty", "Lingual Frenulectomy", "Speech Therapy" and "Myofunctional Therapy". Original articles related to the topic were selected, and a specific protocol was created for data extraction. 798 articles were found. 39 were included after reading the titles and eliminating duplicates, 13 after reading the abstracts, and 7 after reviewing the full texts. Finally, after a cross-reference analysis, 10 studies were included in this review. The importance of speech therapy in the multidisciplinary approach to the lingual frenulum is concluded, addressing aspects of lingual mobility, speech and other orofacial functions altered after the surgical procedure.
Keywords: Ankyloglossia; Lingual Frenulectomy; Lingual Frenuloplasty; Speech Therapy; Myofunctional Therapy